Biomechanical evaluation of surgical techniques for Achilles tendon repair: a laboratory study in bovine tendons - Romancini Daleffe, Murilo; Santos, Arthur Paiva Grimaldi; Kuhn adames, Mario; Roesler, Carlor Rodrigo de Mello; Adames, Mariela Goulart (Journal of the Foot & Ankle, 2023)
Objective: To compare the biomechanical performance of three tendon suture techniques in bovine specimens. The parameters used were elongation after loading, the stiffness of the construct, the maximum force, and the type of suture failure. Method: A complete transection distant 5 cm from the distal bone insertion was made in thirty-six bovine Achilles tendons which were subsequently repaired using Vicryl®#2 sutures in three different ways: Group 1, simple shoelace suture (SS); group 2, triple shoelace suture (TP) and group 3, Carmont & Mafulli suture (CM). All the tendons were submitted to the same biomechanical tests. Results: The tendon elongation was 5.9 mm in group 1 (SS), 3.0 mm in group 2 (TS), and 3.8 mm in group 3 (CM), with statistical significancy between group 2 and groups 1 (p = 0.0037) and 3 (p = 0.0005). Regarding the system stiffness, group 1 presented 23.2 N/mm, group 2, 30.3 N/mm, and group 3, 28.6 N/mm, with statistical significancy of groups 2 (p < 0.0001) and 3 (p = 0.0075) in relation to group 1. The maximum strength results were 158.2 N in group 1, 346.5 N in group 2, and 146.1 N in group 3, with statistical significancy between group 2 and groups 1 (p < 0.0001) and 3 (p < 0.0001). The type of rupture failure was statistically significant among all studied groups. Conclusion: The increased number of sutures decreased the elongation and increased the construct stiffness, com statistical significancy of groups 2 and 3 over group 1. The higher resistance to failure in group 2 (346.5 N) was due to its symmetry and the higher number of sutures passed through both tendon stumps. The TS suture technique showed the lower elongation index (3.0 mm), the greater system stiffness (30.3 N/mm), the maximum force (356.6 N), and proportionality between the types of system failures (suture failure or tendon pullout). Level of Evidence V; Therapeutic Studies; Expert Opinion.